Hydrogel-driven innovations for targeted delivery, immune modulation, and tissue repair in thyroid cancer therapy - Tang, Hanxiao; Tao, Yingli; Zhang, Yongsheng; Ling, Yun; Sheng, Yunjie; Yu, Lingya (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThyroid cancer is the fastest-growing endocrine malignancy globally, with an increasing incidence in younger patients. Conventional therapies, including surgery, radioactive-iodine (RAI) ablation, endocrine suppression, and multi-kinase inhibition, have improved outcomes but are limited by peri-operative morbidity, systemic toxicity, long treatment durations, and the development of drug resistance.ObjectiveThis review synthesizes current advancements in hydrogel-based therapy, focusing on its potential as a multifunctional platform to overcome the challenges in thyroid cancer management. The review highlights the role of hydrogels not only as carriers for various drugs but also as specific agents for thyroid cancer treatment, offering targeted delivery, immune modulation, and tissue repair.ContentModern hydrogels, with their high biocompatibility, tunable mechanical properties, and responsiveness to external stimuli (pH, temperature, light, enzymes), provide site-specific, sustained release of chemotherapeutics, tyrosine kinase inhibitors (TKIs), and 131I. This localised drug delivery increases tumor exposure while sparing vital cervical structures, a critical advantage in thyroid cancer therapy. Composite and in situ-forming hydrogels can also modify the tumour-immune microenvironment, delivering cytokines, checkpoint inhibitors, or vaccine adjuvants to transform immune “cold” lesions, such as poorly differentiated thyroid carcinoma (PDTC), into “hot” immune-responsive sites. Additionally, 3D hydrogel matrices mimic the extracellular matrix, aiding in post-resection tissue repair, preventing cervical adhesions, and enabling the bioprinting of thyroid organoids and CAR-T systems. When integrated with photothermal and photodynamic agents, hydrogels provide synergistic tumour ablation, while formulations with nanosilver or antibiotics help reduce the risk of post-surgical infection.Challenges and OutlookSeveral challenges remain, including optimising the degradation kinetics of hydrogels without compromising their mechanical integrity, improving the loading of hydrophobic TKIs, and better understanding the interactions between hydrogels, the immune system, and tumour tissues in vivo. Large, multi-centre trials are needed to confirm the long-term safety of hydrogel-based therapies and establish their superiority over current standard treatments. Future directions will likely focus on developing “smart” multifunctional hydrogels that can co-encapsulate dual-target inhibitors (e.g., BRAFV600E + MEK), PROTACs, oncolytic viruses, and imaging probes, all informed by single-cell omics-guided patient stratification to enhance therapeutic precision.ConclusionBy integrating precision drug delivery, immune modulation, and tissue engineering into a single platform, hydrogels are positioned to revolutionize the treatment of thyroid cancer. They offer a promising solution for improving locoregional control, minimizing systemic toxicity, and enhancing the survival and quality of life of patients with both differentiated and undifferentiated thyroid cancers. The versatility of hydrogels as carriers for a broad range of therapeutic agents, as well as their specificity for thyroid cancer treatment, highlights their potential to redefine the future of targeted cancer therapies.